2016
DOI: 10.1534/g3.116.031583
|View full text |Cite
|
Sign up to set email alerts
|

Glucose or Altered Ceramide Biosynthesis Mediate Oxygen Deprivation Sensitivity Through Novel Pathways Revealed by Transcriptome Analysis inCaenorhabditis elegans

Abstract: Individuals with type 2 diabetes display metabolic abnormalities, such as hyperglycemia, increased free fatty acids, insulin resistance, and altered ceramide levels, that contribute to vascular dysfunctions and compromised oxygen delivery. Caenorhabditis elegans fed a glucose-supplemented diet or with altered ceramide metabolism, due to a hyl-2 mutation, are sensitive to oxygen deprivation (anoxia). Our experiments showed that the combination of these factors further decreased the anoxia survival. RNA-sequenci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 94 publications
1
13
0
Order By: Relevance
“…Comparison of upregulated nhr-14 genes with C. elegans mutant datasets using WormExp v1.0 showed significant overlap with genes upregulated in nhr-8(hd117) mutants and hyl-2 mutants (Figure 6—source data 4). nhr-8 encodes a nuclear receptor that regulates cholesterol and bile acid homeostasis (Magner et al, 2013) and hyl-2 encodes ceramide synthase that is involved in oxygen deprivation and regulation of innate immune genes (Ladage et al, 2016). Downregulated nhr-14 genes showed significant overlap with genes downregulated in elo-5(gk208) mutants (Kniazeva et al, 2015).…”
Section: Resultsmentioning
confidence: 99%
“…Comparison of upregulated nhr-14 genes with C. elegans mutant datasets using WormExp v1.0 showed significant overlap with genes upregulated in nhr-8(hd117) mutants and hyl-2 mutants (Figure 6—source data 4). nhr-8 encodes a nuclear receptor that regulates cholesterol and bile acid homeostasis (Magner et al, 2013) and hyl-2 encodes ceramide synthase that is involved in oxygen deprivation and regulation of innate immune genes (Ladage et al, 2016). Downregulated nhr-14 genes showed significant overlap with genes downregulated in elo-5(gk208) mutants (Kniazeva et al, 2015).…”
Section: Resultsmentioning
confidence: 99%
“…A mutation in hyl-1 increases oxygen deprivation survival, while a mutation in hyl-2 results in oxygen deprivation sensitivity [15,32]. The sensitivity to oxygen deprivation of a hyl-2 mutant is worsened if the worms are fed a glucose diet, showing an altered expression of genes involved in innate immunity, cuticle function and phase I and II detoxification system [68]. We observed that both hyl-1 and hyl-2 mRNAs were downregulated in glucose-treated worms.…”
Section: Discussionmentioning
confidence: 99%
“…One-day old adult hermaphrodites were collected for mRNA isolation and RT-PCR as previously described [56, 57]. Briefly, mRNA was isolated using TRIzol Reagent (Life Technology, 15596026), NucleoSpin RNA Clean-up (Machenerey-Nagel, 740948-50) and TURBO DNA-free TM kit (Life Technology, AM1907) reagents.…”
Section: Methodsmentioning
confidence: 99%
“…The number of progeny produced by cisd-1(tm4993) and cisd-1(pnIs27) mutants, relative to N2 control, was determined as previously described [57]. At least four synchronized animals were collected at the L4-to-adult molt, placed as individuals onto a NGM plate and allowed to lay eggs over a 24-h period.…”
Section: Methodsmentioning
confidence: 99%